STRATEGI SURVIVALPETANI DALAM PENGOLAHAN LAHAN PASIR: Studi Kasus Tiga Petani Gurem di Lahan Pasir Dusun Bugel II, Kulon Progo - , ARIEF RAMADHAN, Dr. Bambang Hudayana, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The decresing of agricultural lands has become problems for peasant when population growth rapidly. Peasant always choose an adaptation strategy that is able to bring them to the aconomical access for processing and managing all of the natural resources. Those are what peasant do in Bugel II Village, Kulon Progo, D.I. Yogyakarta. This research try to provide an overview or a description the continuity of smallholders farming in the sandy land. This study is also goingto explain some problems which faced by the peasant and their strategies for dealing with these problems in sandy land. This study focus on three smallholders in Bugel II Village to face agricultural problems. All informant were choosen by land ownership which is less than 1.250 m2 and poor household economic categories. Qualitative method was used in this study to explain the smalholders strategy for faces the problems. Data were collected in November until October 2013 with participant observation and in-depth interview. Peasant are faced with the increasingof valuable farm land for their subsistence. Sandy land become an alternative media as agricultural land although regarded as marginal areas because ecologies problems such as fertility level is low, hot, lack of ground water and sea wind was racing so fast that can be easily destroyed crops. Based on that, sandy land requires more intensive management both on capital and labor. Especially, smallholders have limited capital in the form of land and other fixed assets sucs as seeds, fertilizer and labor as the initial process of farm management. Their main agricultural products are chili, watermelon and vegetables which classified as commercial commodities with output and price that can not be prediction. Keywords : smallholders, the environment, capital, strategy